A single-center study evaluating the effect of the controlled adverse environment (CAEsm) model on tear film stability - Abelson R (Dove Medical Press, 2012)
Richard Abelson,1,2 Keith J Lane,3 John Rodriguez,3 Patrick Johnston,3 Endri Angjeli,3 George Ousler,3 Douglas Montgomery11School of Computing, Informatics, and Decision Systems Engineering, Arizona State University, 2Statistics and Data Corporation, Tempe, AZ; 3Ora, Inc, Andover, MA, USAPurpose: To investigate use of an improved ocular tear film analysis protocol (OPI 2.0) in the Controlled Adverse Environment (CAESM) model of dry eye disease, and to examine the utility of new metrics in the identification of subpopulations of dry eye patients.Methods: Thirty-three dry eye subjects completed a single-center, single-visit, pilot CAE study. The primary endpoint was mean break-up area (MBA) as assessed by the OPI 2.0 system. Secondary endpoints included corneal fluorescein staining, tear film break-up time, and OPI 2.0 system measurements. Subjects were also asked to rate their ocular discomfort throughout the CAE. Dry eye endpoints were measured at baseline, immediately following a 90-minute CAE exposure, and again 30 minutes after exposure.Results: The post-CAE measurements of MBA showed a statistically significant decrease from the baseline measurements. The decrease was relatively specific to those patients with moderate to severe dry eye, as measured by baseline MBA. Secondary endpoints including palpebral fissure size, corneal staining, and redness, also showed significant changes when pre- and post-CAE measurements were compared. A correlation analysis identified specific associations between MBA, blink rate, and palpebral fissure size. Comparison of MBA responses allowed us to identify subpopulations of subjects who exhibited different compensatory mechanisms in response to CAE challenge. Of note, none of the measures of tear film break-up time showed statistically significant changes or correlations in pre-, versus post-CAE measures.Conclusion: This pilot study confirms that the tear film metric MBA can detect changes in the ocular surface induced by a CAE, and that these changes are correlated with other, established measures of dry eye disease. The observed decrease in MBA following CAE exposure demonstrates that compensatory mechanisms are initiated during the CAE exposure, and that this compensation may provide the means to identify and characterize clinically relevant subpopulations of dry eye patients.Keywords: tear film break-up time, mean break-up area, interblink interval, controlled adverse environment, ocular protection index